(untitled) (Raparin Journal of Humanities (RJH), 2025)
Knowing and determining the level and the amount of temperature change and the mass of air is an important issue. It can be used to know the amount and the direction of temperature averages, because it has a big impact on the other atmosphere components. Although comprehending the amount and the direction of these temperature levels can be unclear according to the human senses and physiology, but when we do the analysis of these data according to a specific period of time for average temperatures using tables and graphics,we may get more precise results. In this research, which is done in Pishdar district, we relied on metrological stations like (Dukan and Sardasht) for a period of 31 years. In order to get accurate results, we used the quantity analyzing method for analyzing monthly, seasonal and yearly data. The Theoretical framework method for describing important factors affecting the climate change This research shows that the direction of temperature changes is important for temperature levels, with an increase of 3°C over the period of this study in the stations, which is higher than the global average temperature change of the same time.Among the analysed directions, the highest monthly and seasonal temperature change happened in winter,specially in February, with an increase of 4.4°C in Sardasht station. The lowest increase was seen in autumn, specifically in October, with a rise of only 2°C in Dukan station.